Optical characterization of metamaterials - Tan, Sin Nee (2016)
Metamaterials are artificially engineered materials with exceptional properties never seen in conventional materials. In this project, various metamaterial structures are theoretically studied for their ability to enhance photodetectors response. In particular, nanorods, dimers are numerically studied using finite difference time domain (FDTD) simulations. Results obtained are in the form of extinction cross sections and electric field enhancements. Geometrical aspects are varied to study the resultant red and blue shift of resonance which aids the attempt to match the resonance wavelength to the optical response of the photodetector later. During the study of two dimer structure, different light polarization angles were tested. This structure holds a distinctive advantage of resonance able to occur at all angles, a rather practical design for real world application.